RNA-based drugs and regulation: Toward a necessary evolution of the definitions issued from the European union legislation - Guerriaud, Mathieu; Kohli, Evelyne (Frontiers in Medicine, 2022)
Many RNA-based drugs, both vaccines and non-vaccines, are under development or even approved. They include coding mRNAs and non-coding (nc) RNAs among them antisense oligonucleotides (ASOs), small interfering RNAs (siRNAs), micro-RNAs (miRNAs), small activating RNAs (saRNAs), RNA aptamers and RNA guides. According to the European Union (EU) legislation, these products can be currently categorized into different regulatory statuses, depending, for vaccines, on their target (infectious disease or not) and, for other drugs, on how they are obtained (chemically or biologically). This classification is fundamental to the type of marketing authorization (MA), and therefore to the controls to be performed, from preclinical stages through clinical trials to pharmacovigilance, to meet the safety requirements for patients. However, the current rules raise several problems, in particular the risk, because technology is evolving, to have similar RNA drugs being covered by very different legal statuses and the lack of international harmonization. The objectives of this study are (i) to review how RNA medicinal products are currently legally categorized in the EU and especially whether they fall under the status of gene therapy medicinal products (GTMP), a regulatory status belonging to advanced therapy medicinal products (ATMP), (ii) to discuss the issues generated by this classification, with a focus on the heterogeneity of statuses of these products, the differences with the American and ICH definitions and the potential impact on the safety requirements.